Terrestrial planarians (Platyhelminthes, Tricladida, Terricola) from the Iberian Peninsula: new records and description of three new species - Vila-Farré, Miquel; Mateos, Eduardo; Sluys, Ronald; Romero, Rafael (Zootaxa, 2008)
Little is known about the taxonomy and distribution of terrestrial planarians on the Iberian Peninsula. Few studies have tried to investigate the local diversity of these animals, due to both their lack of economic interest and their low abundance. In this study we have made extensive searches and collections of terrestrial planarians from the Iberian Peninsula, thus gathering new information on their taxonomy and biogeography. The study includes the description of three new species of the genus Microplana, viz. Microplana aixandrei sp. nov., Microplana grazalemica sp. nov., and Microplana gadesensis sp. nov. We present distribution maps summarizing published and new records of land planarians. The present work substantially increases our knowledge on this group of animals in Spain and Portugal and at the same time also evidences the scarcity of data and studies on the biology of these organisms.